Company Value In Jakarta Islamic Index Throught Profitability, Environmental Performance And Islamic Corporate Social Responsibility - Febrianti, Nur Anisa; Pura, Rahman; Amin, Asbi (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to examine the influence of profitability, environmental performance and Islamic corporate social responsibility on the company value of the Jakarta Islamic Index. The population in this research are companies listed on the Jakarta Islamic Index (JII) 30 in the vulnerable years 2021-2022, totaling 30 companies. The sample collection technique used was purposive sampling. So the total sample for this research is 48 financial report data and sustainability reports from 24 companies who are listed in the Jakarta Islamic Index (JII) 30 in the vulnerable years 2021-2022. The data uses time series analysis and is analyzed through multiple linear regression analysis. The research results show that profitability has a significant effect on company value; environmental performance has no significant effect on company value and Islamic Corporate Social Responsibility has no significant effect on company value.